Attentional Modulation of Binocular Rivalry - Paffen, Chris; Alais, David (Frontiers in Human Neuroscience, 2011)
Ever since Wheatstone initiated the scientific study of binocular rivalry, it has been debated whether the phenomenon is under attentional control. In recent years, the issue of attentional modulation of binocular rivalry has seen a revival. Here we review the classical studies as well as recent advances in the study of attentional modulation of binocular rivalry. We show that (1) voluntary control over binocular rivalry is possible, yet limited, (2) both endogenous and exogenous attention influence perceptual dominance during rivalry, (3) diverting attention from rival displays does not arrest perceptual alternations, and that (4) rival targets by themselves can also attract attention. From a theoretical perspective, we suggest that attention affects binocular rivalry by modulating the effective contrast of the images in competition. This contrast enhancing effect of top-down attention is counteracted by a response attenuating effect of neural adaptation at early levels of visual processing, which weakens the response to the dominant image. Moreover, we conclude that although frontal and parietal brain areas involved in both binocular rivalry and visual attention overlap, an adapting reciprocal inhibition arrangement at early visual cortex is sufficient to trigger switches in perceptual dominance independently of a higher-level ‘selection’ mechanisms. Both of these processes are reciprocal and therefore self-balancing, with the consequence that complete attentional control over binocular rivalry can never be realized.